2002
DOI: 10.1149/1.1482198
|View full text |Cite
|
Sign up to set email alerts
|

Surface/Chemically Modified LiMn[sub 2]O[sub 4] Cathodes for Lithium-Ion Batteries

Abstract: LiMn 2 O 4 spinel oxide has been surface/chemically modified with Li x CoO 2 , LiNi 0.5 Co 0.5 O 2 , Al 2 O 3 , and MgO using a chemical processing procedure followed by heat-treatment at 300-800°C. The surface/chemically modified samples show much better capacity retention at both 25 and 60°C than does the unmodified LiMn 2 O 4 ͑41% fade in 100 cycles at 60°C͒. Among the various compositions investigated, the LiNi 0.5 Co 0.5 O 2 -modified sample shows superior capacity retention with only 2.8% fade in 100 cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(87 citation statements)
references
References 23 publications
1
86
0
Order By: Relevance
“…TEM observations of the AlPO 4 -coated LLNMC material prepared using this in situ method confirmed the superiority of this procedure in its ability to apply a thin, even layer of AlPO 4 to the surface of the cathode particles ( Figure S2), consistent with reports of other materials synthesized in this manner. 14,18,27,28 This procedure was used for both coated materials to keep their treatments as consistent as possible, even though the borate coating does not precipitate at the initial concentration.…”
Section: Resultsmentioning
confidence: 99%
“…TEM observations of the AlPO 4 -coated LLNMC material prepared using this in situ method confirmed the superiority of this procedure in its ability to apply a thin, even layer of AlPO 4 to the surface of the cathode particles ( Figure S2), consistent with reports of other materials synthesized in this manner. 14,18,27,28 This procedure was used for both coated materials to keep their treatments as consistent as possible, even though the borate coating does not precipitate at the initial concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Choi [5] reported that LiNi 1/3 Co 1/3 Mn 1/3 O 2 gave a capacity of about 184 mAh g −1 over 2.5-4.6 V. However, its capacity fading became faster than that over 2.5-4.4 V. Surface coating was proven to be an effective method to reduce the electrolyte decomposition on the surface of the cathode materials. Experiments such as surface coating of LiMn 2 O 4 with MgO [6], Al 2 O 3 [6], SiO 2 [7], and LiCoO 2 [6,8,9] and surface coating of 5-V materials LiNi 0.5 Mn 1.5 O 4 with ZnO [10] were reported to improve markedly the capacity retention at elevated temperatures. Studies on the surface modifying of LiCoO 2 [11], LiNiO 2 [12], and LiNi 0.8 Co 0.2 O 2 [13,14] were also reported.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the improved elevated temperature properties of LMO coated by other electrode materials is that the surface coating reduces the dissolution of Mn, which results from the suppression of the electrolyte decomposition. The coated electrode materials include LiCoO 2 performed by sol-gel methods [32][33][34] [39], and LiCu x Mn 2−x O 4 [40]. The synthesis methods and the electrochemical performance of coating by other electrode materials are plotted in Table 2.…”
Section: Electrode Materialsmentioning
confidence: 99%